Clinical efficacy of prophylactic intravenous immunoglobulin for elderly DLBCL patients with hypogammaglobulinemia in the COVID-19 pandemic era - Baek, Dong Won; Song, Ga-Young; Lee, Ho Sup; Do, Young Rok; Lee, Ji Hyun; Yhim, Ho-Young; Moon, Joon Ho; Yang, Deok-Hwan (Frontiers in Oncology, 2024)
Background Elderly patients diagnosed with diffuse large B-cell lymphoma (DLBCL) undergoing reduced intensity R-CHOP therapy are at a heightened risk of acquiring infections, notably coronavirus disease 2019 (COVID-19) infection. This study aimed to evaluate the efficacy of intravenous immunoglobulin (IVIG) as prophylaxis against COVID-19 in this vulnerable population. Methods A total of 125 elderly patients with DLBCL undergoing reduced intensity R-CHOP therapy were analyzed in this prospective, multicenter study. Patients with hypogammaglobulinemia were categorized into IVIG and non-IVIG groups, while those with normal immunoglobulin levels constituted the observation group. The study evaluated COVID-19 infection rates, therapy response, and safety outcomes. Results Among the enrolled patients (median age: 77 years), 89 patients (71.2%) presented with hypogammaglobulinemia at diagnosis, and 56 patients enrolled in the IVIG administration group. IVIG administration remarkably reduced COVID-19 infection rates compared to non-IVIG recipients (8.9% vs. 24.6%; p =0.040). Notably, patients over 80 years old were more susceptible to COVID-19. Patients on IVIG exhibited good tolerance with manageable adverse events. Among patients with hypogammaglobulinemia who received IVIG, 40.5% of patients developed additional immunoglobulin deficiencies during chemotherapy. One or more new hypogammaglobulinemia occurred during chemotherapy in 72% of patients with hypogammaglobulinemia who did not receive IVIG, and in 61.3% of patients who did not have hypogammaglobulinemia at diagnosis. Conclusion IVIG showed promise in reducing COVID-19 infections among elderly patients with DLBCL receiving reduced intensity R-CHOP therapy. This highlights IVIG’s potential as a prophylactic measure, necessitating further investigation to optimize dosing, administration schedules, and potential interactions with vaccination strategies.